Christian perspectives in education - Parker, Karen L.; Heady, Emily Walker; Veak, Tyler J., 1963-; Watson, Scott B. (Liberty University, 2007)
This journal provides a forum for practitioners and researchers to explore the application of Christian perspectives in educational settings. "Send out your light and your truth! Let them guide me." Psalm 43:3. Scope: peer-reviewed, scholarly online journal; all educational levels - early childhood through higher education; variety of educational settings - Christian, public, and private education; for practioners and researchers.